26 Outcomes of Systemic Therapy in Metastatic Translocation Renal Cell Carcinoma (tRCC): A Mayo Clinic Retrospective Study - Oluwatayo Adeoye; Abiola Bolarinwa; Albert Jang; Alina Maleski; Dina Elantably; Ruqin Chen; Arnab Basu; Brian Costello; Daniel Childs; Yousef Zakharia; Irbaz Riaz; Winston Tan; et al. (The Oncologist, 2026)
Abstract Background tRCC is a rare subtype characterized by gene fusions involving the microphthalmia-associated transcription factor (MiT) family. Evidence guiding systemic therapy remains limited and is largely derived from small tRCC subsets within larger non-clear cell RCC trials, including CheckMate 920 (2/52, 3.8%), KEYNOTE-B61 (6/158, 3.8%), and a 2024 fusion defined cohort of TFE3 rearranged RCC (n = 38). While these studies suggest activity of combination approaches, they are limited by small sample sizes, heterogeneous populations, and lack of direct comparative analyses. Optimal treatment selection therefore remains unclear. To address this gap, we conducted a retrospective analysis across Mayo Clinic sites comparing outcomes among commonly used systemic therapy classes in metastatic tRCC. Methods We retrospectively reviewed patients with pathologically confirmed tRCC treated across Mayo Clinic sites. Clinicopathologic characteristics and treatment data were extracted from the electronic medical record, with radiographic responses obtained from radiology reports. Regimens were categorized as dual immunotherapy (IO), IO + Tyrosine Kinase Inhibitor (TKI), TKI + mechanistic Target of Rapamycin (mTOR) inhibitor, or monotherapy (single-agent IO or targeted therapy, e.g., Vascular Endothelial Growth Factor Receptor (VEGFR) TKI, mTOR inhibitors, or HIF-2 alpha inhibitors). Outcomes included objective response rate (ORR; complete response + partial response [CR + PR]), disease control rate (DCR; CR + PR + stable disease [SD]), and time to next treatment (TTNT). Categorical variables were compared using chi-square or Fisher’s exact tests. TTNT was estimated by Kaplan-Meier methods and compared using the log-rank test. Results Among 18 patients with metastatic tRCC (median age 38 years, IQR 31-56), 17/18 developed metastases post-nephrectomy and 1/18 presented de novo. First-line therapy was initiated between 2011-2025 (n = 14). In the first-line setting, ORR was 33% (1/3) with dual IO, 17% (1/6) with IO + TKI, 0% (0/4) with monotherapy, and 100% (1/1) with TKI + mTOR (p = 0.20). DCR was higher with TKI-based regimens [83% (5/6) for IO + TKI and 100% (1/1) for TKI + mTOR] compared with dual IO (33%, 1/3) and monotherapy (50%, 2/4) (p = 0.4). By TKI exposure (defined as regimens containing a TKI vs those without a TKI), ORR did not differ (20% [2/10] vs 25% [1/4]; p = 0.8), while DCR was higher with TKI-based regimens (80% [8/10] vs 25% [1/4]; p = 0.05). Median TTNT differed among first-line regimen (log-rank p = 0.008) and was shortest with dual IO (3.5 months, 95% CI 3.2-NR), followed by monotherapy (8.4 months, 95% CI 4.0-NR), IO + TKI (10.0 months, 95% CI 8.4-NR), and TKI + mTOR (10.2 months). Across all lines, ORR favored TKI-based regimens: 66.7% (2/3) with TKI + mTOR, 42.9% (3/7) with IO + TKI, 33.0% (2/6) with dual IO, and 0% (0/10) with monotherapy (p = 0.07). DCR was 100% with IO + TKI (7/7) and TKI + mTOR (3/3), 60% with monotherapy (6/10), and 50% with dual IO (3/6) (p = 0.1). By TKI exposure, ORR was similar [27.8% (5/18) vs 25.0% (2/8); p = 0.88], while DCR was higher with TKI [83.3% (15/18) vs 50.0% (4/8); p = 0.08). At a median follow-up of 34.8 months, TTNT was shortest with dual IO (6 months) vs IO + TKI (NR), TKI + mTOR (13.6 months), and monotherapy (6.9 months) (log-rank p = 0.05). Conclusions In this cohort of metastatic tRCC treated across Mayo Clinic sites, TKI-based regimens were associated with higher disease control and longer treatment durability compared with dual IO or monotherapy. Given the rarity and molecular heterogeneity of tRCC, adequately powered prospective trials are inherently challenging. Retrospective analyses and small prospective studies will likely remain the key sources of evidence to guide treatment selection. These findings are hypothesis-generating and support further evaluation of TKI-based approaches in this rare disease.